DOES INTERNAL CONTROL CAPACITY AND DISCLOSURE OF FINANCIAL PERFORMANCE ON INSTAGRAM CAN INFLUENCE AUDIT OPINION? (STUDY CAPITAL MARKET IN CENTRAL ASIA) - Kizi, Khusanova Khojiyabonu Rovshan; Denny Andriana; R Nelly Nur Apandi (Bajang Institute, 2025)
This study investigates whether internal control capacity and the disclosure of financial performance on Instagram influence audit opinions in companies listed on the Central Asian capital markets. Using a descriptive quantitative approach, data were collected from 21 finance sector companies in Uzbekistan and Kazakhstan, and secondary data were collected from official capital market websites. The results show that both Instagram financial disclosures and total assets do not have a statistically significant effect on audit opinions. The findings suggest that traditional financial strength measures and social media disclosures might not yet play an important role in affecting auditors' judgments in the setting of Central Asia. Limitations of the study are the small sample size and limited data availability, indicating the potential for further research with a broader sample from more sectors and countries. The research contributes to the growing discussion of the evolving role of digital financial communication and internal controls on audit practice in emerging markets.